REVIEW of O.S. Mutieva’s monograph “The Everyday Life of a Dagestan Woman. The Caucasian War and Sociocultural Changes in the 19th Century.” Moscow: Literaturnoe Obozrenie, 2024. ISBN 978-5-4448-2423-8 - Sirazudinova, Saida Valer'evna (History, Archeology and Ethnography of the Caucasus, 2025)
This monograph offers a comprehensive examination of the history of women’s everyday life among the peoples of the Caucasus, drawing on an extensive corpus of approximately 700 historical sources. These include archival materials from 18 distinct collections, primarily retrieved by the author from the Russian State Historical Archives, the Russian State Military Historical Archives, and the Central State Archives of the Republic of Dagestan, which are introduced into scholarly discourse for the first time. The study focuses on women’s everyday experiences and religiosity during the Caucasian War, analyzing sociocultural transformations in the post-reform period and evaluating the war’s impact on the evolving legal and socioeconomic status of women. Particular attention is devoted to women’s perceptions and responses to the extreme conditions of the conflict. The monograph further explores the role of religion in shaping women’s lives, their participation in the war, and their engagement in political spheres. Additionally, it provides a nuanced analysis of transformations in the mentality, religiosity, and behavioral patterns of Caucasian women.